On intimate terms the psychology of difference in lesbian relationships - Burch, Beverly (Univ. of Illinois Press, 1993)
On Intimate Terms looks at the internal logic of lesbian relationships, arguing that they are not patterned after heterosexual ones but rely on the interplay of psychosexual differences between women. The book suggests that everyone seeks psychic complementarity with an Other in intimate relationships as a way of supporting personal growth and development. A complementary partner is one who is different in some individually meaningful way, not necessarily in terms of gender. Drawing upon interviews with individuals and lesbian couples, literature on lesbian psychology, and contemporary psychoanalytic theory, Beverly Burch observes a special attraction between primary lesbians - women who have been attracted to other women from an early age - and lesbians who formerly were heterosexual. This difference may be a source of tension for lovers, but it also attracts and bonds them in conscious and unconscious ways. The intimacy between lesbian partners permits interpersonal exchanges that foster the continuing development of each, according to Burch. This development can occur in three areas, with the significance of each varying from couple to couple. It can be a source of both conscious and unconscious psychosexual exchanges, a way in which each partner can experience "the road not taken" through her relationship with the other. The partners' different histories can reflect different ways of negotiating difference itself, a pivotal theme in the development of adult women. And gender role identities related to different developmental experiences can be played with, expanding the experience of being female in a way that can challenge gender categories.